1986
DOI: 10.3109/10826088609063446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patrons of Hotels with Early Opening and Standard Hours

Abstract: A comparison was made of 72 men who were patrons in hotels with 6 A.M. or 7 A.M. opening, with a control group of 87 men interviewed in nearby hotels with 10 A.M. opening. The two groups were very similar on biographical characteristics, yet the men in the early-opening group consumed significantly more alcohol, had more drinking sessions, spent longer in drinking, and had significantly higher SMAST scores. The early opening was apparently facilitating problem drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The Nordic studies provided some evidence that changes in alcohol availability were particularly likely to affect young or marginalised drinkers [20]. In addition, studies that have examined extensions of opening hours [68,69] have found that problematic drinkers were the most likely to make use of increased availability. This raises the possibility that effects of outlet density which are specific to smaller subgroups may be difficult to detect using population-level data.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…The Nordic studies provided some evidence that changes in alcohol availability were particularly likely to affect young or marginalised drinkers [20]. In addition, studies that have examined extensions of opening hours [68,69] have found that problematic drinkers were the most likely to make use of increased availability. This raises the possibility that effects of outlet density which are specific to smaller subgroups may be difficult to detect using population-level data.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…A series of studies on the effects of increased hours of sale of alcoholic beverages in various cities and states of Australia, reported by Smith (1978Smith ( , 1986Smith ( , 1987Smith ( , 1988aSmith ( ,b,c, 1990, found significant increases in either fatal or injury-producing crashes in the years in which alcohol became more available in comparison with previous years, control times periods or control areas where no changes were introduced. More recently evaluations of the public health and safety impact of extended trading permit hours were conducted in Perth, Australia (Chikritzhs et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to attempts to control access to alcohol (Smith 1986;Forster et al 1995;Norstrom and Skog 2005;Casswell and Thamarangsi 2009), mandatory warnings are used in some jurisdictions. Warning labels seek to inform consumers and hence constitute a form of decisional support.…”
mentioning
confidence: 99%